National Newspaper Portrayal of U.S. Nursing Homes: Periodic Treatment of Topic and Tone - Miller, Edward Alan (Blackwell Publishing Inc, 2012)
CONTEXT: Although observers have long highlighted the relationship of public distrust, government regulation, and media depictions of nursing-home scandals, no study has systematically analyzed the way in which nursing homes have been portrayed in the national media. This study examines how nursing homes were depicted in four leading national newspapers—the New York Times, Washington Post, Chicago Tribune, and Los Angeles Times—from 1999 to 2008. METHODS: We used keyword searches of the LexisNexis database to identify 1,704 articles pertaining to nursing homes. We then analyzed the content of each article and assessed its tone, themes, prominence, and central actor. We used basic frequencies and descriptive statistics to examine the articles’ content, both cross-sectionally and over time. FINDINGS: Approximately one-third of the articles were published in 1999/2000, and a comparatively high percentage (12.4%) appeared in 2005. Most were news stories (89.8%), and about one-quarter were on the front page of the newspaper or section. Most focused on government (42.3%) or industry (39.2%) interests, with very few on residents/family (13.3%) and community (5.3%) concerns. Most were negative (45.1%) or neutral (37.0%) in tone, and very few were positive (9.6%) or mixed (8.3%). Common themes were quality (57.0%), financing (33.4%), and negligence/fraud (28.1%). Both tone and themes varied across newspapers and years. CONCLUSIONS: Overall, our findings highlight the longitudinal variation in the four widely read newspapers’ framing of nursing-home coverage, regarding not only tone but also shifts in media attention from one aspect of this complex policy area to another. The predominantly negative media reports contribute to the poor public opinion of nursing homes and, in turn, of the people who live and work in them. These reports also place nursing homes at a competitive disadvantage and may pose challenges to health delivery reform, including care integration across settings.